2019
DOI: 10.1038/s41598-018-36884-1
|View full text |Cite
|
Sign up to set email alerts
|

N-glycans of the microalga Chlorella vulgaris are of the oligomannosidic type but highly methylated

Abstract: Microalgae of the genus Chlorella vulgaris are candidates for the production of lipids for biofuel production. Besides that, Chlorella vulgaris is marketed as protein and vitamin rich food additive. Its potential as a novel expression system for recombinant proteins inspired us to study its asparagine-linked oligosaccharides (N-glycans) by mass spectrometry, chromatography and gas chromatography. Oligomannosidic N-glycans with up to nine mannoses were the structures found in culture collection strains as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 34 publications
0
33
0
1
Order By: Relevance
“…The combination of genomic annotation and experimental evidence has revealed some details about N-glycans in some species; however, more information is needed. Analysis of five different microalgal species [94,[107][108][109][110][111] showed two different glycosylation pathways based on presence or absence of the GnT I enzyme. The green microalgae C. reinhardtii and C. vulgaris, and the red microalga Porphyridium purpureum lack GnT I, which has been validated experimentally [94,107,108,111].…”
Section: N-glycosylationmentioning
confidence: 99%
See 2 more Smart Citations
“…The combination of genomic annotation and experimental evidence has revealed some details about N-glycans in some species; however, more information is needed. Analysis of five different microalgal species [94,[107][108][109][110][111] showed two different glycosylation pathways based on presence or absence of the GnT I enzyme. The green microalgae C. reinhardtii and C. vulgaris, and the red microalga Porphyridium purpureum lack GnT I, which has been validated experimentally [94,107,108,111].…”
Section: N-glycosylationmentioning
confidence: 99%
“…In this pathway, the 5 Man and 2 GlcNAc N-linked protein is subjected to the action of xylosyltransferases (XyT) and methyltransferases (MeT), leading to unique N-linked structures containing methylated mannoses linked to one or two xyloses ( Figure 1). The structures vary slightly among these microalgae, with different possible locations of the xylose residues [94,107,108,111]. On the other hand, Baïet and colleagues [109] demonstrated that GnT I is present and active in the diatom P. tricornutum.…”
Section: N-glycosylationmentioning
confidence: 99%
See 1 more Smart Citation
“…With regards to microalgae, studies have demonstrated that the Golgi maturation of N ‐glycans in microalgae like Volvox carteri , Porphyridium sp., Phaeodactylum tricornutum , Botryococcus braunii , Euglena gracilius , Chlorella vulgaris , also give rise to a large variety of oligosaccharides ranging from oligomannosidic to complex‐type N ‐glycans decorating with GlcNAc, xylose, fucose, aminoethylphosphonate moieties and/or O ‐methylated mannose residues (Balshüsemann and Jaenicke, ; Baïet et al , ; Levy‐Ontman et al , , ; O’Neill et al , ; Schulze et al , ; Mócsai et al , ). Among microalgae, Chlamydomonas reinhardtii is the best studied so far as it has been chosen as a model laboratory system for many biological processes ranging from photosynthesis over flagellar movement including acclimation to nutrient deficiency (Rochaix, ; Merchant et al , ; Marshall, ; Harris, ).…”
Section: Introductionmentioning
confidence: 99%
“…Frontiers in Bioengineering and Biotechnology | www.frontiersin.org (Guarnieri et al, 2011(Guarnieri et al, , 2013Sibi et al, 2014;Li et al, 2015b;Ouyang et al, 2015;Henard et al, 2017;Zuñiga et al, 2018;Mocsai et al, 2019) Chloroidium sp. Katz et al, 2007;Jia et al, 2009Jia et al, , 2016Gu et al, 2014;Ge et al, 2016;Lv et al, 2016;Zhao et al, 2016;Wei et al, 2017b;Wang et al, 2019d Emiliana (Benner et al, 2013;Rokitta et al, 2014;Hunter et al, 2015;McKew et al, 2015;Wördenweber et al, 2018) Fistulifera solaris (JPCC Wang et al, 2004;Tran et al, 2009;Peled et al, 2011;Gu et al, 2014;Recht et al, 2014;Su et al, 2014;Gao et al, 2016;Baumeister et al, (Chen et al, 2014;Ge et al, 2014;Jungandreas et al, 2014;Rosenwasser et al, 2014;Yang et al, 2014;Abida et al, 2015;Alipanah et al, 2015;Feng et al, 2015;Bai et al, 2016;…”
Section: Metabolomics and Metabolic Modelsunclassified